ASSESSMENT OF KNOWLEDGE REGARDING END-OF-LIFE CARE AMONG NURSES - TEHSEEN , I; REHMAT , S; NIGAR , Z; TASNEEM, SS; JABEEN, R (Biological and Clinical Sciences Research Journal, 2024)
Background: End-of-life care is a critical component of nursing practice, aimed at providing compassionate support to patients in the final stages of life. This care focuses on ensuring patients' comfort, preserving their dignity, and addressing their emotional needs during this sensitive time. Objective: This study aims to evaluate nurses' knowledge level regarding end-of-life care practices. Methods: A cross-sectional study was conducted in a tertiary care hospital involving 108 patients who received end-of-life care over a six-month period from January to June 2023. Data collection methods included structured interviews and questionnaires directed at both the patients and their primary nurses. The data were analysed using SPSS version 25, with descriptive statistics to summarise the findings. Inferential statistics, including the chi-square test, were used to identify significant factors influencing end-of-life care quality. Results: The study involved 108 participants, primarily females (93.52%) and a minority of males (6.48%). The analysis showed that 85% of the patients experienced notable relief from physical symptoms, particularly in pain management. Moreover, 75% of the patients highlighted the importance of psychological support, while 70% emphasised the significance of spiritual care in contributing to their overall satisfaction. Including family members in care planning positively affected the emotional well-being of 65% of the patients. Key factors such as effective communication between nurses and patients (80%) and the use of individualised care plans (78%) were significantly associated with an improved quality of end-of-life care (p < 0.05). Conclusion: End-of-life care in nursing is crucial for enhancing patients' comfort, dignity, and emotional well-being. Effective pain management, psychological support, and involving family members in care planning are vital for delivering high-quality end-of-life care. Further training and resources for nurses are recommended to maintain and improve these practices.